Economics Against Tyranny: A Reassessment of the Liberal Order of Mises and Hayek - Bastos, João Pedro Pedro (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The present work analyses the writings of Mises and Hayek on the relation between a liberal order and a free market, and the role of economic theory in advancing the appreciation of democratic institutions, considering the context of their expositions. Subsequently, it tries to address the contemporary state of political and economic affairs in the light of their teachings, highlighting missing aspects in today’s public debate and what should be taken into account for a coherent defense of the liberal order.